"Unattended" retirement: Lifestyle migration and precarity of the Houniao. Issue 8 (6th July 2020) - Chen, Jingfu; Wang, Bingyu
Abstract: This paper unpacks the precarity of lifestyle migrants through the study of the Houniao ("snowbirds"), mostly retirees leading seasonal travel between north and south China. Focusing on the Houniao in Sanya, it explores the production and negotiation of their precarity at multiple scales. Firstly, it investigates how they encounter "precarious privilege" in Sanya's changing urban space and respond to government control and rising living expenses. Secondly, it examines their vulnerability intensified by health decline and constraints of place‐based care networks and their agency to rebuild local supporting systems. Thirdly, it explores their contested relationships with Sanya and the sense of marginality and how they develop Houniao ‐based social networks. This paper highlights the significance of space/place and human agency in understanding the dynamic process in which precarity is generated and negotiated. Additionally, it provides a wider perspective on the complexity of precarity in lifestyle migration by focusing on the China context.